EVALUASI KEANDALAN SISTEM PROTEKSI KEBAKARAN DITINJAU DARI SARANA PENYELAMATAN DAN SISTEM PROTEKSI PASIF KEBAKARAN DI GEDUNG LAWANG SEWU SEMARANG - Djaka Anugrah Hidayat; Suroto Suroto; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Safety factor is one of requirements that must be met in every building, where fire prevention is one of the aspects. Safety for the occupants of the building should also be taken into account. Public space such as such as Lawang Sewu Building, which are categorized as a heritage building, are protected by the government and its usage are regulated by the law. The purpose of this study is to analyze the reliability of fire protection system in terms of fire rescue facility and passive fire protection system in Lawang Sewu Building. The study is conducted in descriptive design with qualitative approach. The main subject is the Management of Lawang Sewu Museum under Preservation and Architecture Unit of PT KAI (Indonesian National Railway Company), with triangulation subjects from Tour Guides under the Tourism Office and Security Guards. The reliability of fire protection system is assessed using Technical Guideline of Fire Safety Inspection on Buildings (Pd-T-11-2005-C) from the Ministry of Public Work. The result showed that Fire Rescue Facility was in good condition with category compliance rate of 86,06% from the assessment criteria, and Passive Fire Protection System in fair condition with category compliance rate of 67,96% from the assesment criteria. The Management of Lawang Sewu Museum should conduct emergency response simulation to improve preparedness in rescuing visitors and assets, replacing safety signs such as Fire Extinguisher signs and evacuation route signs, and consider to rearrange the placement of fire extinguishers to maximize immediate fire response.